1971
DOI: 10.1002/ijch.197100099
|View full text |Cite
|
Sign up to set email alerts
|

Inductive Effects on Molecular Ionization Potentials. V. Hydrogen Sulfide and Aliphatic Thioethers

Abstract: The ionization energies of thioethers, R 2S, have been correlated with the polar substituent constants and the inductive substituent constants. Good correlations are obtained which indicate that the effect of alkyl substituents on the S·atom is primarily an inductive one.we have shown recently that the ionization energies of alcohols [6] We now denonstrate that the ionization energies of thioethers, R 1S, are also linear functions of both 0* and 0 1 , The gas-phase expulsion of an electron from the non-bonding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1973
1973
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…More than 30 years ago, Crowell and colleagues [5–7] reported that CVB3 binding to HeLa cells was unaffected by trypsin treatment. Experiments reported here reveal that the CAR is cleaved within 15 min following addition of trypsin to HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 30 years ago, Crowell and colleagues [5–7] reported that CVB3 binding to HeLa cells was unaffected by trypsin treatment. Experiments reported here reveal that the CAR is cleaved within 15 min following addition of trypsin to HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments conducted before isolation of CAR found that the binding of CVB to HeLa cells is not altered by trypsin treatment [5–7], and in vitro experiments often use cultured cells exposed to virus only hours after subculture with trypsin. The experiments reported here reveal that CAR is not resistant to trypsin, and treatment of HeLa cells with trypsin alters the expression of this viral receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism e, somewhat modified since the time it was first proposed,3 is the mechanism that we currently favor, and involves the heterolytic autoionization of S2082" into sulfate and the zwitterionic sulfur tetroxide. The very first step probably gives an intimate ion pair, followed perhaps by subsequent equilibria involving solvated ionic species, but the subsequent equilibria, for the sake of simplicity, will not be shown: ~03-S-^0^-0 S03~S042-+ +0-SO3"" (slow) (12) and the rate -d[S20821/dz = fc2[R2SO] [SO40] = fci[S2082"] [R2S0]/([R2S0] 4 k^SOf']/^} (13) But since the rate in any given run is fc[S2082'], it follows that the observed rate constant is given by k = fc,[R2SO]/([R2SO] 4 k.x[S0421 /k2) (14) identical with eq 2 if b = fc_i[S042_]//c2.…”
Section: Reproducibility Of Resultsmentioning
confidence: 99%
“…Because our general experimental approach (1-3) generate's a larg'e number 0 f TLC fractions of widely different radioactivity, an economi~al, convenient and rapid technique for collecting and transfering TLC zones to liquidscintillation vials was required. Many zone collectors have been described (4)(5)(6)(7)(8)(9)(10)(11), but were judged inadequate because of one or more of the following disadvant~ges: potential contamination by adsorbent from previous use adhering to the device, clogging of fritted glass filters, need for cleaning and drying prior to reuse, or need for a separate device for each sample. This report describes a device ~vhich is free of these disadvantages and is ~uitable for rapid collectiort and transfer of a series of zones.…”
Section: Zone Collector and Transfer Device For Tilin-:--layer Chromamentioning
confidence: 99%